Utility of Nosodes in Homoeopathy (Homoeopathy for All, 2025)
Nosodes are the Homoeopathic remedies prepared from the disease substance or products. This implies using potentially dangerous noxious materials as a basis for a potentized remedy. Nosodes are homeopathic preparations of organic materials derived from inactivated disease products, cultures of microorganisms (e.g., bacteria, fungi, and viruses) parasites, infected or pathologically changed material, or decomposition products from humans or animals. In homeopathic practice, nosodes play an important and indispensable role. They are constantly indicated as common, intercurrent, anti-miasmatic, or acute remedies, etc., depending on the physician’s perception. In this article, we sought to find the actual use made of nosodes in homeopathic practice.
Keywords: Nosodes; Homoeopathy practice; homoeoprophylaxis, Miasmatic treatment, Epidemics